Draft Annual Plan 1993-1994 Volume-III Details of Schemes Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1993)
The programme for 8th Plan includes opening of 25 Pre-Primary schools, appointment of 25 Part-time teachers and 25 Part-time Ayahs, procurement of Play materials, toys, picture books, radio, audio visual materials etc. for the use of the existing and new schools. Further efforts are made to develop more capacity for the training of Pre-school teachers and the PSTs already appointed under this scheme in the existing training Institute.
Andaman and Nicobar Administration